Challenges to Qur’anic Authenticity in Modern Scientific Interpretation - Saddaqat Hussain (Ma'had Aly As'adiyah Sengkang, 2026)
Contemporary scientific tafsir often rests on a weak premise: if a scientific claim does not appear explicitly in the Qur’an, the text must contain a deficiency. This premise misreads the Qur’an’s primary function, which provides spiritual and moral guidance rather than detailed scientific explanation. Scientific theories change, so interpretations that tie verses to unsettled hypotheses risk generating doubts. Yet established discoveries have not invalidated Qur’anic claims. When a reading seems to conflict with a verse, the error lies with the interpreter, not the Qur’an. Therefore, scientific interpretation must remain bounded by clear Qur’anic language and by empirical findings that have reached broad scientific acceptance, and it should avoid speculative extensions. This study examines how pseudo-scientific interpretations create contemporary doubts about Qur’anic authenticity.